Pengaruh Edukasi Latihan Star Excursion Balance Test (SEBT) Terhadap Penguatan Stabilitas Ankle pada Pemain Sepak Bola SSB Mandiri Medan - Jhon Roby Purba; Theresia Anggriani H; Tuty Swarni Sinaga; Indra Alamsyah; Rudianto Rudianto (STIKes Ibnu Sina Ajibarang, 2023)
Ankle injuries are among the most common injuries experienced by adolescent soccer players, often caused by poor stability and neuromuscular control. Ankle instability not only affects athletic performance but also increases the risk of recurrent injuries. One effective preventive and rehabilitative approach is dynamic balance training, such as the Star Excursion Balance Test (SEBT). This study aimed to analyze the effect of education and SEBT exercises on ankle stability enhancement in U-15 soccer players at SSB Mandiri Medan. This research employed a pre-experimental design with a one-group pre-test and post-test approach, involving 20 male participants aged 13–15 years. The SEBT training program was conducted for four weeks, with a frequency of three sessions per week. Ankle stability was measured using reach distances in all eight directions of SEBT and the Cumberland Ankle Instability Tool (CAIT) questionnaire. Data were analyzed using a paired t-test to compare pre- and post-intervention results. The findings showed a significant improvement in SEBT reach scores (p < 0.05) and increased CAIT scores, indicating enhanced functional ankle stability. These results suggest that structured education and SEBT training can serve as an effective strategy for injury prevention and performance enhancement in young soccer athletes.